A new species of Pediobius (Hymenoptera: Eulophidae) from Epilachna (Coleoptera: Coccinellidae) in Costa Rica - Hanáon, C.
(Es, En)
ilus., 8 ref.
Keywords: HYMENOPTERA; INSECTA; TAXONOMIA; PARASITOIDES; COSTA RICA; PEDIOBIUS NISHIDAI